Pitfalls in diagnosis and management of suspected urinary tract infection in an urban tropical primary care setting - Alison A Jackson; Pauline Siew Mei Lai; Aqtab Mazhar Alias; Nadia Atiya; Siti Nurkamilla Ramdzan; Tun Firzara Abdul Malik; Fadzilah Hanum Mohd Mydin; Haireen Abd Hadi; Sajaratulnisah Othman (Journal of Infection in Developing Countries)
Introduction: Diagnosis and management of urinary tract infection (UTI) are complex, and do not always follow guidelines. The aim of this study was to determine adherence to the 2014 Malaysian Ministry of Health guidelines for managing suspected UTI in a Malaysian primary care setting.